Sex and grade differences in cyberbullying of Spanish students of 5th and 6th grade of Primary Education - Delgado Domenech, Beatriz; Escortell Sánchez, Raquel (Anales de Psicología / Annals of Psychology, 2018)
Cyberbullying is a recent phenomenon that has a great impact on the development and well-being of children. The objective of the present study is to analyze the differences in cyberbullying (victims, bullies, and bystanders) according to the sex and grade of the participants. The sample consisted of 548 students from 5th and 6th grade of primary education. The results indicate that girls are significantly more victimized than boys, and score higher on five victimizing behaviors, seven bullying behaviors, and four behaviors of observation of cyberbullying. The students of the two courses present similar scores in being a victim, a bully, and a bystander of cyberbullying. However, 6th-graders are more victimized through manipulated videos and death threats and perform more behaviors related to blackmailing to not reveal secrets through the Internet, whereas 5th-gradersstand out due to more blackmail or threats through calls or messages. In relation to the bystanders, 5th-graders claim they observe more anonymous calls and sexual harassment. The evidence found is discussed, establishing possible directions for future studies, as well as the practical implications for the development of effective intervention programs.